BIMBINGAN DAN PENYULUHAN TENTANG PENTINGNYA LOYALITAS PELANGGAN MELALUI KUALITAS PELAYANAN PADA BENGKEL SUDIMORO DIESEL DI MALANG - Joko Samboro; Zubaidi Zubaidi; Abdullah Helmy; Yosi Afandi; Musthofa Hadi (P3M Politeknik Negeri Malang, 2023)
The purpose of this PKM is to find the problems faced by the Sudimoro Diesel workshop business on Jalan Sudimoro Dalam No.35 RT.6 RW.7 Sudimoro, Kel. Mojolangu, Kec.Lowokwaru Malang City and at the same time provide the right solutions in order to achieve increased knowledge and skills in the field operational, especially in the field of marketing management, especially Service Quality and Customer Loyalty. The methods used are: observation, to observe activities carried out both in the field of marketing, then interviews, explored to find problems and solutions that will be offered and simulations, to find the most appropriate alternative to market goods more effectively. With the completion of this service program, entrepreneurs are expected to pay attention to how to make customers satisfied, then customers voluntarily recommend to others, and customers will return to the garage, if in the future they have problems with their cars, Partners are expected to pay attention to aspects of service quality, such as: appearance when serving customers, especially the clothes still haphazard, then given a uniform, there is no place to sit/wait then made a place.